Ferrocene-Containing DNA Monolayers: Influence of Electrostatics on the Electron Transfer Dynamics - Magriñá, Ivan; Ortiz, Mayreli; Simonova, Anna; Hocek, Michal; O' Sullivan, Ciara K; Forster, Robert J (Langmuir, 2021)
A 153-mer target DNA was amplified using ethynyl ferrocene dATP and a tailed forward primer resulting in a duplex with a single-stranded DNA tail for hybridization to a surface-tethered probe. A thiolated probe containing the sequence complementary to the tail as well as a 15 polythimine vertical spacer with a (CH2)6 spacer was immobilized on the surface of a gold electrode and hybridized to the ferrocene-modified complementary strand. Potential step chronoamperometry and cyclic voltammetry were used to probe the potential of zero charge, PZC, and the rate of heterogeneous electron transfer between the electrode and the immobilized ferrocene moieties. Chronoamperometry gives three, well-resolved exponential current-time decays corresponding to ferrocene centers located within 13 Å (4 bases) along the duplex. Significantly, the apparent standard heterogeneous electron transfer rate constant, kappo, observed depends on the initial potential, i.e., the rate of electron transfer at zero driving force is not the same for oxidation and reduction of the ferrocene labels. Moreover, the presence of ions, such as Sr2+, that strongly ion pair with the negatively charged DNA backbone modulates the electron transfer rate significantly. Specifically, kappo = 246 ± 23.5 and 14 ± 1.2 s-1 for reduction and oxidation, respectively, where the Sr2+ concentration is 10 mM, but the corresponding values in 1 M Sr2+ are 8 ± 0.8 and 150 ± 12 s-1. While other factors may be involved, these results are consistent with a model in which a low Sr2+ concentration and an initial potential that is negative of the PZC lead to electrostatic repulsion of the negatively charged DNA backbone and the negatively charged electrode. This leads to the DNA adopting an extended configuration (concertina open), resulting in a slow rate of heterogeneous electron transfer. In contrast, for ferrocene reduction, the initial potential is positive of PZC and the negatively charged DNA is electrostatically attracted to the electrode (concertina closed), giving a shorter electron transfer distance and a higher rate of heterogeneous electron transfer. When the Sr2+ concentration is high, the charge on the DNA backbone is compensated by the electrolyte and the charge on the electrode dominates the electron transfer dynamics and the opposite potential dependence is observed. These results open up the possibility of electromechanical switching using DNA superstructures.
Keywords: Electrons; transport elektronů; Electrodes; Metallocenes; DNA; metaloceny; elektrody; Static Electricity; Electron Transport; elektrony; statická elektřina